Reinvestigation on the state-of-the-art nonaqueous carbonate electrolytes for 5 V Li-ion battery applications - Xu, Wu (2013)
The charging voltage limits of mixed-carbonate solvents for Li-ion batteries were systematically investigated from 4.9 to 5.3 V in half-cells using Cr-doped spinel cathode material LiNi0.45Cr0.05Mn1.5O4. The stability of conventional carbonate electrolytes is strongly related to the stability and properties of the cathode materials in the de-lithiated state. This is the first time report that the conventional electrolytes based on mixtures of EC and linear carbonate (DMC, EMC and DEC) can be cycled up to 5.2 V on LiNi0.45Cr0.05Mn1.5O4 for long-term cycling, where their performances are similar. The discharge capacity increases with the charging cutoff voltage and reaches the highest discharge capacity at 5.2 V. The capacity retention is about 87% after 500 cycles at 1C rate for all three carbonate mixtures in half-cells when cycled between 3.0 V and 5.2 V. When cycled to 5.3 V, EC-DMC still shows good cycling performance but EC-EMC and EC-DEC show faster capacity fading. EC-DMC and EC-EMC have much better rate capability than EC-DEC. The first-cycle irreversible capacity loss increases with the cutoff voltage. The “inactive” conductive carbon is also partly associated with the low first-cycle Coulombic efficiency at high voltages due to electrolyte decomposition and possible PF6- anion irreversible intercalation.